'Catching Ovulation': Exploring Women's Use of Fertility Tracking Apps as a Reproductive Technology. (September 2020) - Hamper, Josie
Smartphones are increasingly entangled with the most intimate areas of everyday life, providing possibilities for the continued expansion of digital self-tracking technologies. Within this context, the development of smartphone applications targeted at female reproductive health are offering novel forms and practices of knowledge production about reproductive bodies and processes. This article presents empirical research from the United Kingdom on women's use of fertility tracking applications, known more generally as fertility apps, while trying to conceive. Drawing on material from interviews with women who had experience of using fertility apps, I demonstrate the significance of this particular form of fertility tracking for the embodied shift from pregnancy prevention to actively facilitating pregnancy, participants' sense of self and identity and how they perceived the reproductive potentiality of their bodies. I argue that fertility apps are significantly involved in making fertility cycles known and thus configuring the pre-pregnant reproductive body.